(untitled) (Revista Electrónica Calidad en la Educación Superior, 2024)
This research aims to identify the differences and similarities between the model of the Central American Agency for Postgraduate Accreditation (ACAP) and the model of the Honduran System for Accreditation of Quality in Higher Education (SHACES). The research methodology is descriptive with a qualitative approach using the comparative method. According to the results, both models are based on the same theory: Stufflebeam’s Systemic Model of Context, Inputs, Processes, and Outputs (CIPP). In addition, both structure aspects relate to teaching, research, linkage, academics, administrative management, and internationalization. Among the differences, it is highlighted that accreditation with ACAP is voluntary, while with SHACES it is mandatory.